From the anesthesiologist perspective retrospective analysis of perioperative complications of transsphenoidal pituitary surgery - (:unkn) unknown (My University, 2006)
Amaç: Pitüiter cerrahi adenomların tiplerine göre, farklılık gösteren morbiditeler nedeniyle anestezi doktoru için yoğun uğraş gerektiren girişimlerdir. Bu çalışmanın amacı, transsfenoidal cerrahi sırasında ortaya çıkan komplikasyonları anestezi doktorunun bakış açısıyla değerlendirmektir. Yöntem: 1 Ocak 2002-1 Ocak 2006 tarihleri arasında transsfenoidal hipofiz cerrahisi geçiren ve ASA skoru I-II olan 82 hasta retrospektif olarak çalışmaya alındı. Her hasta için; demografik özellikler, havayolu sağlanması, cerrahi süre, kardiyovasküler ve elektrokardiyografik anormallikler, patolojik tanı ve perioperatif dönemde ortaya çıkan komplikasyonlar kaydedildi. Bulgular: Anestezi indüksiyonunu takiben 4 hastada medikal tedaviye cevap vermeyen ağır bradikardi ve geniş QRS kompleksin eşlik ettiği ventriküler premature atımlar görüldü. Üç hasta entübasyon sırasında problem yaşadı. Oniki hastada ise submukozal enjeksiyon sonrasında hipertansif yanıt gözlendi. Erken postoperatif dönemde 2 hastada (%2.4) geçici diabetes insipid görüldü. Hastaların hiçbirinde rinore veya nazal kanama görülmedi. Bu bağlamda 21 hastada (%25.6) perioperative dönemde komplikasyon oldu. Sonuç: Anestezistler zor entübasyon, vazokonstriktör eklenmiş lokal anesteziğin submukozal enjeksiyonuna bağlı hipertansif yanıt ve anestezi indüksiyonu sonrasında subklinik kardiyak patolojilerin klinik bulgu verir hale gelme olasılığını göz önünde bulundurmalıdır.

Objective: Pituitary surgery presents unique challenges for the anesthesiologist due to the distinct medical co-morbidities associated with various adenomas. Aim of this study was to investigate the perioperative complications throughout the transsphenoidal pituitary surgery from the anesthesiologists perspective. Methods: Retrospectively, 82 ASA physical status I-II patients, underwent transsphenoidal surgery date between 1st Jan 2002-1st Jan 2006, were included in the study. The following general information was recorded for each patient: demographic data, airway management, cardiovascular and electrocardiographic abnormalities, duration of procedures, pituitary pathology, and any complications at the perioperative period. Results: After induction, four patients developed severe bradycardia and ventricular premature beats with bizarre QRS complex with hypotension, non-responsive to atropine and ephedrine. Three patients experienced intubation problem. In 12 patients, following submucosal injection a hypertensive response was observed. Only two patients (2.4%) had experienced temporary diabetes mellitus after surgery. Overall, 21 patients (25.6%) experienced complications during perioperative period of transsphenoidal pituitary surgery. Conclusion: Anesthesiologist must be wary of the possibility of difficult intubation, hypertensive episode at the time of intranasal submucosal injection of vasoconstrictor-supplemented local anesthetic, and hemodynamic and electrocardiographic abnormalities related to the underlying overlooked cardiac pathologies at any time during surgery.
Anestezist gözüyle transsfenoidal hipofiz cerrahisinde perioperatif dönemde görülen komplikasyonlarının geriye dönük değerlendirilmesi
Keywords: Genel ve Dahili Tıp